2015
DOI: 10.3109/19401736.2015.1046160
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of commercially important lobster species from Indian coast inferred from mitochondrial and nuclear DNA sequences

Abstract: Lobsters constitute low-volume high-value crustacean fishery resource along Indian coast. For the conservation and management of this declining resource, accurate identification of species and larvae is essential. The objectives of this work were to generate species-specific molecular signatures of 11 commercially important species of lobsters of families Palinuridae and Scyllaridae and to reconstruct a phylogeny to clarify the evolutionary relationships among genera and species included in this study. Partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Earlier studies and reports of the genus Thenus in India were based on the single species-Thenus orientalis (Chacko, 1967;Deshmukh, 2001;Kizhakudan et al, 2004a;Vijayakumaran & Radhakrishnan, 2011). However, in view of the species revision of the genus (Burton & Davie, 2007), the species distributed and caught widely along the coast was ascertained to be T. unimaculatus (Jeena et al, 2011). This bottom-dwelling species forms an important fishery along the northwest and southeast coasts (Radhakrishnan et al, 2013) and prefers sandy and muddy habitat of 10-50 m depth (FAO, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies and reports of the genus Thenus in India were based on the single species-Thenus orientalis (Chacko, 1967;Deshmukh, 2001;Kizhakudan et al, 2004a;Vijayakumaran & Radhakrishnan, 2011). However, in view of the species revision of the genus (Burton & Davie, 2007), the species distributed and caught widely along the coast was ascertained to be T. unimaculatus (Jeena et al, 2011). This bottom-dwelling species forms an important fishery along the northwest and southeast coasts (Radhakrishnan et al, 2013) and prefers sandy and muddy habitat of 10-50 m depth (FAO, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the maximum ratio for TL/TW was found to be 0.33 which suggest that the value of this ratio need to be increased. During the period of our study, we did not come across any samples of T. orientalis and all samples were having the morphological and morphometric characters similar to (Jeena et al, 2011). COI gene is widely employed in molecular studies in T. unimaculatus (Burton and Davie, 2007;Palero et al, 2008;Jeena et al., 2011;Iamsuwansuk et al, 2012;Wongruenpibool and Denduangboripant, 2013;Jeena et al, 2016a;Jeena et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Burton &Davie (2007) described T. unimaculatus based on the morphological and mitochondrial DNA sequence analysis. This species is currently known to be distributed in locations in the Indo-West Pacific Oceans near Thailand, the United Arab Emirates and Mozambique (Burton and Davie 2007), Thailand (Iamsuwansuk et al, 2012;Wongruenpibool and Denduangboripant, 2013) and India (Jeena et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The scyllarid lobster, Thenusunimaculatus, described earlier as Thenusorientalis (Chhapgar and Deshmukh 1964) is commonly known as sand lobster, slipper lobster, or shovel-nosed lobster. The species of shovel nosed lobsters available in Indian waters has been con rmed as Thenus unimaculatus (Jeena et al 2011). It is one of the important commercially exploited lobster species in India.…”
Section: Introductionmentioning
confidence: 99%